2021
DOI: 10.1093/ajhp/zxab099
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing likelihood of COVID-19 vaccination: A survey of Tennessee adults

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 20 publications
4
59
2
2
Order By: Relevance
“…This finding was in contrast with prior studies which have shown greater COVID-19 hesitancy among those living in a more ruralized area. 26 , 27 However, we did find differences in general vaccine confidence, with rural area residents reporting significantly less trust in vaccines in general compared to those living in urban areas. To our knowledge, this is the first study to document a difference in general vaccine confidence among rural and urban respondents.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding was in contrast with prior studies which have shown greater COVID-19 hesitancy among those living in a more ruralized area. 26 , 27 However, we did find differences in general vaccine confidence, with rural area residents reporting significantly less trust in vaccines in general compared to those living in urban areas. To our knowledge, this is the first study to document a difference in general vaccine confidence among rural and urban respondents.…”
Section: Discussioncontrasting
confidence: 57%
“…Main sample features of the studies included in the analysis are shown in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ,…”
Section: Resultsmentioning
confidence: 99%
“…This finding can be attributed to the fact that people are concerned about the distrust of vaccine safety and vaccine novelty which are documented as deterrents of vaccination [ 33 , 34 ]. Additionally, they have access to few published scientific facts on the efficacy and safety of the COVID-19 vaccines [ 24 , 35 ]. This could also be explained in part, by the lack of trust in the government regarding the response activities to the pandemic [ 36 - 39 ].…”
Section: Discussionmentioning
confidence: 99%